Avian diversity in geothermal power plant areas: Case studies in Kamojang, Darajat, and Gunung Salak, West Java, Indonesia - TEGUH HUSODO; KHEMAL PASHA MOCHTAN; Sya Sya Shanida; SYAHRAS FATHIN AMINUDDIN; INDRI WULANDARI; IRWANANDA SATRIA PUTRA; ERRI NOVIAR MEGANTARA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Husodo T, Mochtan KP, Shanida SS, Aminuddin SF, Wulandari I, Putra IS, Megantara EN. 2020. Avian diversity in geothermal power plant areas: Case studies in Kamojang, Darajat, and Gunung Salak, West Java, Indonesia. Biodiversitas 21: 1049-1059. Land cover changes that occur in the development of industrial areas have impact on the quality of biophysical and socio-economic environments. This study aimed to investigate the diversity of birds (avifauna) in three geothermal power plant areas in West Jawa Province, Indonesia (i.e., Kamojang, Darajat, and Gunung Salak). Transect and spotlighting methods were conducted in this study. We found that areas around geothermal power plant in Gunung Salak had the highest diversity of bird species with 105 species from 43 families, followed by Kamojang with 82 species from 34 families, and Darajat with 80 species from 40 families. In total, there were 134 species from 51 families in which two species are Endangered (EN) under the IUCN Red List category, five are endemic to Java, 11 are protected by CITES Appendix II and 14 are protected by national regulations. The presence of some birds was an indicator of ecosystem condition and functioning, including indicator of food chain, quality of water, quality of natural habitat, condition of riparian habitat, and the condition of open or disturbed habitat. Some birds were also associated with particular habitats, such as natural forests, riparians, a combination of natural forests and open habitats, tea plantations, and craters. The results of this study can be used as baseline information about the state of the surrounding environment in the three geothermal power plant areas and as a reference in biodiversity management in the future.